1989
DOI: 10.1111/j.1540-6288.1989.tb00353.x
|View full text |Cite
|
Sign up to set email alerts
|

The Day the United States Defaulted on Treasury Bills

Abstract: Because of severe technical difficulties, the U.S. government was unable to repay investors in Treasury bills (T‐bills) in late April through early May, 1979. This incident led to a 60 basis point increase in T‐bill rates at the initial occurrence of the default. Unlike other information effects of that era, such as Henry Kaufman's predictions or Paul Volcker's “Saturday night special,” this increase in rates was not offset by a subsequent decrease in rates after the Treasury cured the default. The default app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 7 publications
2
15
0
Order By: Relevance
“…The first option, if used unwisely can lead to hyperinflation making paper money worthless while the use of the second option is limited by the checks and balances that exist in a democracy to counteract high taxes. Due to these reasons among others and the fact that the US Treasury defaulted earlier (Zivney and Marcus, 1989) and came very close to defaulting a second time (Nippani et al, 2001) the question of default-free Treasury securities has come into question. Zivney and Marcus (1989) show that there was a 60 basis point increase in Treasury bill rates at the initial occurrence of a default by the United States Treasury in May 1979.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The first option, if used unwisely can lead to hyperinflation making paper money worthless while the use of the second option is limited by the checks and balances that exist in a democracy to counteract high taxes. Due to these reasons among others and the fact that the US Treasury defaulted earlier (Zivney and Marcus, 1989) and came very close to defaulting a second time (Nippani et al, 2001) the question of default-free Treasury securities has come into question. Zivney and Marcus (1989) show that there was a 60 basis point increase in Treasury bill rates at the initial occurrence of a default by the United States Treasury in May 1979.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thakor (2006) who discussed the work of Kotlikoff (2006) disagrees, but cautions against excessive borrowing by the U.S. Treasury. Zivney and Marcus (1989) examined the impact of a temporary, technical default by the U.S. government and showed that yields increased following the default. Nippani, Liu and Schulman (2001) showed that under some circumstances, risk premiums were charged on short-term U.S. Treasury obligations, and Nippani and Smith (2010) showed the same for long-term U.S. Treasury debt.…”
Section: Discussionmentioning
confidence: 99%
“…This debt has been rated AAA since ratings began and while the U.S. Treasury debt had been placed on "Creditwatch" earlier by rating agencies like Moody's (Note 5) it has never relinquished its AAA rating prior to 8-5-2011. There was a default by the U.S. Treasury, a technical one in 1979 (Zivney and Marcus, 1989). Evidence of default risk premiums on short-term and long-term U.S. Treasury securities was documented by Nippani, Liu and Schulman (2001) and Nippani and Smith (2010).…”
Section: Analysis Of Day 1 Negative Returnsmentioning
confidence: 99%
“…Results from studies using a VAR-framework are more 1 Zivney and Marcus (1989) find that the only known instance of technical default in the U.S. in 1979 caused a 60 basis point increase in T-bill rates. 2 The Council of Economic Advisers (2003) estimates that interest rates rise by about 3 basis points for every additional $200 billion in government debt.…”
Section: Introductionmentioning
confidence: 99%